Relations of the weekly external training load indicators and running performances in professional soccer matches - Modric, T.; Versic, S.; Sekulic, D. (SportMont, 2021)
The aim of this study was (i) to examine associations between training load during the week and match outcomes; (ii) to evidence position-specific differences between playing positions of training load and match running performances in top-level soccer/football. Training load and match running performances were evaluated through external load parameters: total-distance-covered, distance covered by walking, jogging, running, high-intensity-running (high-speed-running + sprinting); the number of accelerations, high-intensity-accelerations, decelerations, and high-intensity- decelerations. All data were obtained via the Global Positioning System from twelve matches of the highest-level Croatian soccer competition and from training sessions in the preceding weeks. The players (age: 23.57±2.84 years) were divided into five playing positions: central defenders (n=18), full-backs (n=20), central midfielders (n=26), wing midfielders (n=5) and forwards (n=9). Significant ANOVA differences (p<0.05) were found in all external match load variables, while in weekly training sessions only in high-intensity-running, high-intensity-accelerations, and high-intensity- decelerations distinguished players across their playing positions. Inverse correlation for most of the external load parameters and positive correlation for the number of training sessions with match outcome was evidenced. Chances of positive match outcome were greater in weeks when the team participated in fewer training sessions and consequently had lower values of external training load.